Beezus and Ramona [compact disc, unabridged] - Cleary, Beverly (HarperChildrens Audio, 2010)
Beezus Quimby wants to be a good older sister, but little Ramona makes it so hard. She has to be the most embarrassing sister ever. Although Ramona isn't trying to get into trouble, her unmatchable imagination usually carries her there.